2003
DOI: 10.1046/j.1460-9568.2003.03058.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine receptor supersensitivity in rat subthalamus after 6‐hydroxydopamine lesions

Abstract: The subthalamic nucleus (STN) receives direct dopaminergic innervation from the substantia nigra pars compacta, but the importance of this input in the pathophysiology of parkinsonism remains to be determined. We used whole-cell patch-clamp recordings in brain slices to study presynaptic dopaminergic modulation of synaptic inputs to the STN in unilateral 6-hydroxydopamine (6-OHDA)-lesioned rats. Here, we report that dopamine was more potent for inhibiting GABA IPSCs and glutamate EPSCs in the STN ipsilateral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 51 publications
(63 reference statements)
1
18
0
Order By: Relevance
“…The change in SNr Glu levels after dopaminergic denervation may be attributable to an effect restricted to the STN or related structures. Many studies have reported direct dopaminergic innervation of the STN (Brown et al, 1979;Meibach and Katzman, 1979;Campbell et al, 1985;Hassani et al, 1997;Smith et al, 1998), which may control STN neuron activity directly or via presynaptic modulation of neurotransmitter release (Kreiss et al, 1997;Ni et al, 2001;Shen et al, 2003;Cragg et al, 2004). The level of GABA in the SNr also increased in hemiparkinsonian rats.…”
Section: Changes In Basal Glu and Gaba Level Induced By Snc Lesioningmentioning
confidence: 97%
“…The change in SNr Glu levels after dopaminergic denervation may be attributable to an effect restricted to the STN or related structures. Many studies have reported direct dopaminergic innervation of the STN (Brown et al, 1979;Meibach and Katzman, 1979;Campbell et al, 1985;Hassani et al, 1997;Smith et al, 1998), which may control STN neuron activity directly or via presynaptic modulation of neurotransmitter release (Kreiss et al, 1997;Ni et al, 2001;Shen et al, 2003;Cragg et al, 2004). The level of GABA in the SNr also increased in hemiparkinsonian rats.…”
Section: Changes In Basal Glu and Gaba Level Induced By Snc Lesioningmentioning
confidence: 97%
“…The cortical projection to the striatum is thought to be modified in PD, toward weakened and enhanced influences to the D1 and the D2 segments, respectively (West and Grace 2002). In the STN, both inhibitory and excitatory projections seem to be enhanced under dopamine-depleted states (Shen and Johnson 2000;Shen et al 2003;Floran et al 2004). Finally, in the GPe, it has been found that the inhibitory connection from the striatum is enhanced in such states (Cooper and Stanford 2001), and the input from the STN is hyperactive (Johnson and Napier 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The release of the NG2 ectodomain from NG2 glia was augmented by treatments with depolarizing agents or glutamate in vitro [98]. Along this line, the expression of the neuromodulatory/neuroprotective peptide galanin significantly increased in NG2 glia upon experimental cortical spreading depression [169]. These observations suggest that activity dependent/synapse-mediated signals converging on NG2 glia may dynamically regulate their secretory activity and homeostatic functions.…”
Section: Neuregulinsmentioning
confidence: 75%
“…study and CM of cultured rat NG glia [165] Synaptogenesis and synaptic plasticity [166], oligodendroglial and neuronal survival [167,168] Galanin mRNA and protein expr. in adult mouse NG2 glia [169] Modulation of neuronal activity [170] Chromogranin B, Chgb Gene expr. study of freshly sorted adult human NG2 glia [125] Neurotransmission [171,172] Chromogranin C, Chgc Gene expr.…”
Section: Neuregulinsmentioning
confidence: 99%